Kajian Kapasitas Kelompok Tiang pada Tanah Lunak Menggunakan Skala Kecil Laboratorium - Naibaho, Andry Galardo; Waruwu, Aazokhi (Department of Civil Engineering, Diponegoro University, 2021)
Soft clay is one type of subgrade that is problematic in infrastructure development. Pile reinforcement is an alternative to stabilize and increase the bearing capacity of soft clay soils. This study is expected to determine the capacity of the pile group from observations through a small-scale laboratory model and its comparison with the results of the analysis. Reinforcement of the piles used are concrete piles and wooden piles. The research was conducted through model testing on single piles and group piles in soft clay soil. The piles have a length of 20 cm and a diameter of 2 cm with the number of 1, 2, 4, and 9 piles. The study results show that the overall bearing capacity of the observed results is not much different from the results of the analysis. The average bearing capacity of the wooden and concrete piles is 20% and 18% greater than the analysis. The increase in pile capacity for each additional number of piles from the observations is not as high as the analysis. There is a tendency for the soil in the pile group to move down together, so that the capacity value of the pile group on soft clay is smaller than the single pile capacity value multiplied by the number of piles in the pile group.